Please solve q 56 ?

enter image source here

2 Answers
May 12, 2018

option (4) is acceptable

Explanation:

a+b-c

=(sqrta+sqrtb)^2-(sqrtc)^2-2sqrt(ab)

=(sqrta+sqrtb+sqrtc)(sqrta+sqrtb-sqrtc)-2sqrt(ab)

=(sqrta+sqrtb+sqrtc)(sqrtc-sqrtc)-2sqrt(ab)

=(sqrta+sqrtb+sqrtc)xx0-2sqrt(ab)

=-2sqrt(ab)<0

So a+b-c<0=>a+b < c
This means sum of the lengths of two sides is less than the third side . This is not possible for any triangle.
Hence formation of triangle is not possible i.e option (4) is acceptable

May 24, 2018

Option (4) is correct.

Explanation:

Given,

rarrsqrt(a)+sqrt(b)=sqrtc

rarr(sqrt(a)+sqrt(b))^2=(sqrtc)^2

rarra+2sqrt(ab)+b=c

rarra+b-c=-2sqrt(ab)

rarra+b-c<0

rarra+b<c

So, no formation of triangle is possible.